2018
DOI: 10.1074/jbc.m117.812289
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 4–induced ryanodine receptor 2 oxidation and sarcoplasmic reticulum Ca2+ leakage promote cardiac contractile dysfunction in sepsis

Abstract: Studies suggest the potential role of a sarcoplasmic reticulum (SR) Ca leak in cardiac contractile dysfunction in sepsis. However, direct supporting evidence is lacking, and the mechanisms underlying this SR leak are poorly understood. Here, we investigated the changes in cardiac Ca handling and contraction in LPS-treated rat cardiomyocytes and a mouse model of polymicrobial sepsis produced by cecal ligation and puncture (CLP). LPS decreased the systolic Ca transient and myocyte contraction as well as SR Ca co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 64 publications
(71 reference statements)
1
31
0
Order By: Relevance
“…15 A recent study showed that TLR4 activation induced Ca 2+ leakage via regulating FKBP12.6 dissociation from RyR2 in septic cardiomyocytes. 45 Thus, we hypothesized that DEX may attenuate myocardial I/R injury by inhibiting [Ca 2+ ]i overload via TLR4-mediated FKBP12.6/RyR2 signaling pathway. In addition to the action on α2 adrenergic receptors, DEX may act on ion channels and membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…15 A recent study showed that TLR4 activation induced Ca 2+ leakage via regulating FKBP12.6 dissociation from RyR2 in septic cardiomyocytes. 45 Thus, we hypothesized that DEX may attenuate myocardial I/R injury by inhibiting [Ca 2+ ]i overload via TLR4-mediated FKBP12.6/RyR2 signaling pathway. In addition to the action on α2 adrenergic receptors, DEX may act on ion channels and membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown beneficial effect of TLR4 inhibitor (TAK-242) through preventing SR Ca 2+ leak in septic mice. Coincidentally, TLR4 deficiency significantly improved cardiac function and corrected abnormal Ca 2+ handling in septic mice (Yang et al, 2018), which indicate that the critical role of TLR4-dependent SR Ca 2+ leak in the development of SCM.…”
Section: Imbalance Of Calcium Homeostasis In Cardiac Myocytesmentioning
confidence: 80%
“…The linkage between activations of TLRs/its downstream signals and SCM has been established from current investigations. Inhibition of TLR4 has shown protective effect on SCM in experimental animal models (Fenhammar et al, 2014;Yang et al, 2018). Based on those findings, targeting TLRs to develop new therapeutic approaches is promising.…”
Section: Toll-like Receptors In Cardiomyocytesmentioning
confidence: 91%
See 1 more Smart Citation
“…Ca 2+ plays an important role in stimulus-response reactions of cells as a second messenger, which involves in several elements, such as LTCC, mitochondria, transient receptor potential channel and ryanodine receptor [51][52][53][54]. In present study, we focused on the effects of XBXT on CaM/CaMKII/ERK1/2 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%